Chapter Employability and Competence. But for which Europe? - Polenta, Stefano (Studies on Adult Learning and Education, 2018)
This paper proposes to understand the concepts of employability and competence, placing them within the neoliberal scenario that today characterizes the European project, aiming to promote maximum competitiveness in a condition of increasing austerity and a reduction in workers' rights